Different radical initiation techniques of hydrosilylation reactions of multiple bonds in water: dioxygen initiation - Postigo, Jose Alberto (2010)
The relevance of radical initiation metodologies for the classical hydrosilylation reactions of organic compounds bearing C[BOND]C multiple bonds is due to the need to come up with newer and more effcient methods to effect this reaction, on account of its applications on surface chemistry. In the past, when organic solvents were employed, thermal and photochemical methods for the chain initiation reaction have been documented (thermal and photochemical decomposition of azo compounds). We herein present the dioxygen-initiation technique of the classical radical hydrosilylation reaction of C[BOND]C triple bonds with tris(trimethylsilyl)silane ((Me3Si)3SiH) in water. This initiation technique is confronted with the photochemical radical initiation in the absence of a chemical radical precursor other than the silane and also confronted with the classical thermal initiation triggered by the decomposition of an azo compound, both performed in water. The radical-based dioxygen initiation methodology studied in water is shown to afford the highest Z:E stereoselective ratios of hydrosilylated alkenes.